Counterfeiting of Weel-Known Brands in Indonesia: Legal Protection? - Gunawan Pratama; Asmin Patros (Legal Spirit, 2023)
The use of well-known brands is now starting to bloom, and this is none other than because it promises big benefits that will be obtained when using well-known brands instead of using their brands. One of the reasons why many industries use well-known brands for their products is to make them easy to sell. This study uses normative legal research methods to examine the protection of well-known brands in Indonesia. The results of this study indicate that trademark protection is provided after the trademark owner registers his trademark. Law Number 20 of 2016 needs to define well-known brands clearly. Well-known marks, namely the rejection of an application that is basically the same or wholly with a well-known Mark for similar goods and services is carried out with due observance of the general provisions. public knowledge about the mark in the field of business concerned. In addition, attention is also paid to the reputation of a well-known brand that is obtained due to vigorous and large-scale promotions, investments in several countries in the world that are carried out by the owner and are accompanied by proof of registration. brand in several countries.